The Effect of Endoscopic Bariatric and Metabolic Therapies on Gastroesophageal Reflux Disease - Su-Young Kim (Medicina, 2021)
Obesity is a chronic disease that is becoming increasingly more prevalent and is associated with many health problems, such as metabolic syndrome. The treatment options for obese patients include lifestyle modification, medications, endoscopic bariatric and metabolic therapies (EBMTs), and surgery. In particular, EBMTs have an excellent therapeutic effect and are less invasive than bariatric surgery. Although it is clear that EBMTs are relatively safe procedures, they can result in several adverse events. Among them, the relationship between EBMTs and gastroesophageal reflux disease (GERD) is unclear. Several studies have demonstrated that an intragastric balloon (IGB) may worsen GERD. There are a few studies on the effects of endoscopic sleeve gastroplasty (ESG) on GERD, but the linking evidence is insufficient. However, the conclusion is not simple. Because obesity is an important cause of GERD, and GERD naturally improves with weight loss after EBMTs, it is not easy to evaluate accurately the effect of EBMTs on GERD. This review aimed to discuss the effect of EBMTs on GERD and suggest future research directions.